Caracterización y evaluación de quitosano como potencial biomaterial para aplicaciones en ingeniería de tejidos - Álzate Díaz, Luisa Fernanda (Universidad de San Buenaventura - Cali, 2016)
In this research the characterization and evaluation of commercial and experimental films of chitosan as a biomaterial for potential applications in tissue engineering was performed. The experimental chitosan was obtained from the cell wall of the fungus Aspergillus niger. This was grown and processed in the facilities of the Universidad San Buenaventura, Cali, Colombia, Instituto Tecnológico de Mérida, Mérida, Mexico, and Centro de Investigación Científica de Yucatán, Merida, Mexico. The methodology is based on a process of basic hydrolysis using 40% NaOH at 95 ° C for 5 hours. Subsequently, an acid treatment was carried out with 10% HCl and then chitosan precipitation using 30% NaOH was made. Chitosans were characterized by infrared spectroscopy (FTIR), nuclear magnetic resonance and thermogravimetric analysis (TGA). Solutions with trifluoroacetic acid / dichloromethane was prepared at 70/30 respectively and both experimental and commercial chitosan 7% w / v. The commercial chitosan is formed by electrospinning, producing films of continuous fibers (of submicron lengths) forming a highly porous three-dimensional membrane. The films were characterized by SEM and SEM-EDX and stress tests.